Enhancement of the internal quantum efficiency in strongly coupled P3HT-C60 organic photovoltaic cells using Fabry–Perot cavities with varied cavity confinement - de Jong Lianne M. A.; Berghuis Anton Matthijs; Abdelkhalik Mohamed S.; van der Pol Tom P. A.; Wienk Martijn M.; Janssen Rene A. J.; Gómez Rivas Jaime (Nanophotonics, 2024)
The short exciton diffusion length in organic semiconductors results in a strong dependence of the conversion efficiency of organic photovoltaic (OPV) cells on the morphology of the donor-acceptor bulk-heterojunction blend. Strong light–matter coupling provides a way to circumvent this dependence by combining the favorable properties of light and matter via the formation of hybrid exciton–polaritons. By strongly coupling excitons in P3HT-C60 OPV cells to Fabry–Perot optical cavity modes, exciton-polaritons are formed with increased propagation lengths. We exploit these exciton–polaritons to enhance the internal quantum efficiency of the cells, determined from the external quantum efficiency and the absorptance. Additionally, we find a consistent decrease in the Urbach energy for the strongly coupled cells, which indicates the reduction of energetic disorder due to the delocalization of exciton–polaritons in the optical cavity.